The stability of PGV-0 (Pentagamavunon-0) as an Antiinflammatory drug in liquid dosage forms - Tedjo Yuwono; R. A. Oetari (Indonesian Journal of Pharmacy, 2004)
PGV-0 is a curcumin derivate, a synthetic compound which may be a candidate of a new drug. This substance has a potent inflammatory effect with a very low toxicity.One of the first step which must be searched for a candidate of drug, is to perform a stability study. There are many degraded drugs causing the adverse reactions. Most of them could be the initiator in forming an antigen at anaphylactic reaction or allergic reaction. Further more some of the degraded drugs are very toxic. So, the study of degradation or the stability investigations of a new drug should be carried out.The PGV-0 stability in a buffer solution at pH 10,0 had been studied by an accelerated temperature method. The temperatures were held at 50°, 55° and 60° C. The intact PGV-0 has been analysed by HPLC. The results then were used to define the shelf-life, the half life and the activation energy of the degradation of PGV-0.It was evident that PGV-0 was unstable in aqueous solution, the shelf-life was only 45.3 hours, the half-life was 299 hours and the activation energy was 14,2 kkal mol-1. Because the PGV-0 was not stable in aqueous solution, it is suggested that this substance should be made into solid dosage forms instead of the liquid dosage forms.Key word : PGV-0, stability, solution